KARAKTERISTIK KIMIA DAN SENSORI SNACK BAR DARI LABU KUNING DAN KACANG HIJAU - Alhadi, Muhamad; Fitriani, Shanti; Rahmayuni, Rahmayuni (Jurnal Sains dan Teknologi Pangan, 2021)
Snack bar is a solid rod-shaped food, made from a mixture of dry ingredients such as cereals, nuts, grains and fruits which formed into one with binder.  The purpose of this research was to get the best formulation of yellow pumpkin flour and green beans flour on the chemical and sensory characteristics of snack bar.  This research was conducted experimentally by using a completely randomized design (CRD) with four treatments and four replications.  The treatments in this research was the ratio of yellow pumpkin flour and green beans flour, which were LK1 (80:20), LK2 (60:40), LK3 (40:60) and LK4 (20:80).  Data obtained were statistically analyzed using analysis of variance (ANOVA).  If the F count is greater than or equal to the F table, further tests will be continued with duncan’s new multiple range test (DNMRT) at 5% level. The best treatments in this research was the ratio of yellow pumpkin flour and green beans flour (20:80) where 18.29% moisture content, 2.49% ash content, 7.83% protein content, 13.16% fat content, 2.01% crude fiber content, 58.22% carbohydrat content, 382.69 kcal energy.  The descriptive test showed that the snack bar had yellowish brown color, a little flavoring green beans, solid, a little green bean taste and overall assessment hedonically was favored by panelists.Keywords: snack bar, yellow pumpkin, green beans